Simulation FW61 for the manuscript: "Magnitude of the 8.2 ka event freshwater forcing based on stable isotope modelling and comparison to future Greenland melting" - Aguiar, Wilton; Meissner, Katrin J.; Montenegro, Alvaro; Prado, Luciana F.; Wainer, Ilana; Carlson, Anders E.; Mata, Mauricio M. (Zenodo, 2021)
Simulation FW61 produced with the oxygen-isotope enabled University of Victoria Earth System Model. The simulation starts 9 kiloyears before the present (...-0949.01.01.nc) and runs until 7 kiloyears before the present. The outputs are annual means (tsi) and annual fields (tavg).